Visible light communications with single-photon avalanche diodes - Alsolami, I (2014)
This thesis explores the use of single-photon avalanche diodes (SPADs) for visible light communications (VLC). The high sensitivity of SPADs can potentially enhance the performance of VLC receivers. However, a SPAD-based system has challenges that need to be addressed before it can be considered as a viable option for VLC. The first challenge is the susceptibility of SPAD-based receivers to variations in ambient light. The high sensitivity of SPADs is advantageous for signal detection, but also makes SPADs vulnerable to variations in ambient light. In this thesis, the performance of a SPAD-based receiver is investigated under changing lighting conditions. Analytical expressions to quantify performance are derived, and an experiment is conducted to gain further understanding of system performance. It is shown that a SPAD-based receiver is highly sensitive to illumination changes when on-off keying (OOK) is employed, and that pulse-position modulation (PPM) is a preferred modulation scheme as it is more robust. The second challenge is broadcasting to SPAD-based receivers with different capabilities. A traditional broadcasting scheme is time-sharing, whereby a transmitter sends data to receivers in an alternating manner. Broadcasting to SPAD-based receivers is challenging as receivers may have diverse capabilities. In this thesis, a new multiresolution modulation scheme is proposed, which can potentially improve system performance over the traditional timesharing approach. The performance of the proposed scheme is analyzed, and a proof-of-concept experiment is performed to demonstrate its viability.